Causes of in-hospital delay for door-to-needle times in patients presenting with acute ST-Elevation Myocardial Infarct in Rural Malaysia - Mohd Shah, Azarisman Shah; Ngow, Harris Abdullah; PA, Melor; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Sapari, S.; K, Khairi; S, Noorfaizan; Maskon, Oteh (Mosby Inc., 2008)
Study Objective: Background: In developing countries such as Malaysia, the primary mode for revascularization is via thrombolytic therapy. The Malaysian Clinical Practice Guideline on acute ST-elevation myocardial infarction advised the implementation of a 30-minute door-to-needle time. This study aims to evaluate the mean door-to-needle times and the reasons for in-hospital delays. Methods: Ninety four patients with acute ST elevation myocardial infarction patients were screened and 75 patients were recruited in this prospective observational study. The mean door-to-needle times were recorded and the reasons for delays in door-to-needle times were elucidated. Results: The majority of patients were male (89.3%), of Malay ethnicity (84%), presenting with anterior MI (69.3%) with a mean age of 57.0 9.52 years. The mean door-to-needle time was 80.54 84.8 minutes. Only 20% achieved the 30- minute door-to-needle time and only 65.3% achieved the 60 minute door-to-needle time. The reasons for late thrombolysis were quoted as late referrals from AE (50%), hypertensive emergency (22%), resuscitation (17%) and others (11%). Conclusion: There is significant in-hospital delay in administrating thrombolytic agents for patients presenting with acute ST-elevation myocardial infarction. Some of the delays were unavoidable (hypertensive emergency and hypotension or VT/VF requiring resuscitation) but the majority of the delay is due to late referrals from AE to attending cardiology on-call officers.